2021
DOI: 10.37358/rc.21.4.8452
|View full text |Cite
|
Sign up to set email alerts
|

Study on Thermal and Flame Retardant Properties of Phosphorus-containing Polyimides

Abstract: The present study aimed to design macromolecular architectures having imide core in the main chain and bearing two 9,10-dihydro-oxa-10-phosphaphenanthrene-10-oxide heterocycles in the side chain of each structural units as a synergetic two components key factor to induce attractive flame retardant properties in the resulted materials. The synthesis pathway consisted in the classical polycondensation reaction strategy using a phosphorus-containing diamine synthesized in the laboratory and three commercial dianh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…2DOPO-NH 2 was synthesized according to previously published procedures starting from 4,4’-diaminobenzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene- 10-oxide [ 24 , 25 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…2DOPO-NH 2 was synthesized according to previously published procedures starting from 4,4’-diaminobenzophenone and 9,10-dihydro-9-oxa-10-phosphaphenanthrene- 10-oxide [ 24 , 25 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of the PI(1–4) polyimides studied in the current work has been described in detail in our previously published paper [ 27 ]. Nevertheless, in the present work, the PI(1–4) have been prepared via casting from solutions technique followed by the thermal imidization in film state instead of thermal imidization in solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the PVA/OA-4, the T 5% is lower probably the presence of the high content of ze-Ag in the sample leads to the catalysis of this. The weight loss of the PFR-4 took place between 267 • C and 361 • C, corresponding to the release of small molecules and breakdown of the weak bonds such as P-O-C and P-C [40][41][42][43][44][45]. Also, from the TG curves it can be observed that the PFR-4 can reduce the T 5% of the PVA/OA-0 and promote the formation of the carbonaceous layers on the surface.…”
Section: Thermal Stabilitymentioning
confidence: 96%